Adult T-Cell Lymphoma/Leukemia Presenting as Isolated Central Nervous System T-Cell Lymphoma. (23rd December 2014) - Ma, Wei-Li; Li, Chi-Cheng; Yu, Shan-Chi; Tien, Hwei-Fang
Abstract : Adult T-cell leukemia/lymphoma (ATLL) is a T-cell neoplasm, associated with infection by the retrovirus human T-lymphotropic virus type 1 (HTLV-1). Central nervous system (CNS) involved by ATLL is often occurred in advanced disease, such as acute and lymphomatous variants. On the other hand, isolated CNS lymphoma is rare. We repot a 50-year-old woman who presented with multiple infiltrative brain lesions on the magnetic resonance (MR) imaging. Results of initial biopsy of brain tumor indicated CNS vasculitis. The patient received one course of high-dose methotrexate and MR imaging of brain revealed remission of infiltrative lesions. Two years later, new brain lesions were detected. Histopathologic examination of specimens via craniotomy revealed T-cell lymphoma. The patient responded poorly to subsequent chemotherapy, and salvage whole-brain irradiation was performed. Six months later, the patient had hepatosplenomegaly, hypercalcemia, and multiple lymphocytes with a cloverleaf appearance in circulation. Results of flow cytometry analysis of peripheral blood indicated ATLL and antibodies to human T-lymphotropic virus type 1 (HTLV-1) were detected. Clinicians should screen HTLV-1 infection when patients are diagnosed with peripheral T-cell lymphoma. Combined antiviral therapy and intensive chemotherapy may improve the outcomes of ATLL.